Experience of application of modern innovative teaching methods in higher medical school studying the discipline" Histology, cytology and embryology" - Popko, S. S.; Aksamytieva, M.; Yevtushenko, V.; Попко, Світлана Сергіївна; Євтушенко, Валентина Михайлівна (My University, 2021)
Modern realities of life require the widespread use of modern innovative methods, primarily distance learning in Ukrainian higher medical school. The article describes the features of distance learning of the discipline "Histology, cytology and embryology" in conditions of quarantine. Many years of experience in the use of innovative technologies at the Zaporizhzhia State Medical University of the Ministry of Health of Ukraine contributed to the effective and timely organization of distance learning at the Department of Histology, Cytology and Embryology. The use of a personal competence approach to each student contributed to a better assimilation of the educational material allowed them to gain high quality and deep knowledge.